Seed Characteristics and Testa Textures some Taxa of Genus Lathyrus L. (Fabaceae) from Turkey - (:unkn) unknown (FRIENDS SCIENCE PUBL, 2011)
Seed morphology and testa texture of 18 wild taxa of Lathyrus L., distributed in Turkey, such as L. niger (L.) Bernh. subsp. niger, L. palustris L. subsp. palustris, L. digitatus (Bieb.) Fiori, L. pratensis L., L. laxiflorus (Desf.) O. Kuntze subsp. laxiflorus, L. tuberosus L., L. undulatus Boiss. (endemic), L. sylvestris L., L. sphaericus Retz., L. setifolius L., L. annuus L., L. gorgoni Parl. var. pilosus C. C. Townsend, L. cicera L., L. hirsutus L., L. clymenum L., L. ochrus (L.) DC., L. nissolia L., L. aphaca L. var. affinis (Guss.) Arcang were examined. The morphological characters of the seeds; general shape, size, colour, surface shape, length and width of the hilum were observed under stereomicroscope. The testa patterns, papillae shape, papillae density, ribbed and waxy layer were examined using scanning electron microscope (SEM). The general shapes of the seeds have been determined as elliptical, elliptical-circular and elliptical-angular. The surface shape is smooth, tuberculate and reticulate. Furthermore, some photos, taken under a stereomicroscope and SEM have been added. We suggest that the seed morphology and testa texture could be used as definers in the identification of Lathyrus taxa. c 2011 Friends Science Publishers
Keywords: Lathyrus; Seed morphology; Testa texture; Turkey; SYSTEMATIC SIGNIFICANCE; MORPHOLOGY; VICIEAE